The development of an Irish census-based social class scale - O'Hare, Aileen; Whelan, Christopher T.; Commins, Patrick (Economic & Social Studies, 1991)
This paper outlines the reasons for, and steps taken, to develop an Irish census-based social class scale. The willing participation of the Central Statistics Office in reorganising its occupational categories to devise this scale marks an innovative contribution to social research. The resulting classification has a validity in an Irish context beyond that of alternative scales and should be an asset to researchers in facilitating a more comprehensive and revealing analysis of census occupational data than has hitherto been feasible. The scale is based on the neo-Weberian concept of class and has six categories.
Keywords: census data; social scale; Ireland; statistical methods